A LASSO-Derived Risk Model for Subclinical CAC Progression in Asian Population With an Initial Score of Zero - Wu, Yun-Ju; Mar, Guang-Yuan; Wu, Ming-Ting; Wu, Fu-Zong (Frontiers in Cardiovascular Medicine, 2021)
Background This study is aimed at developing a prediction nomogram for subclinical coronary atherosclerosis in an Asian population with baseline zero score, and to compare its discriminatory ability with Framingham risk score (FRS) and atherosclerotic cardiovascular disease (ASCVD) models. Methods Clinical characteristics, physical examination, and laboratory profiles of 830 subjects were retrospectively reviewed. Subclinical coronary atherosclerosis in term of Coronary artery calcification (CAC) progression was the primary endpoint. A nomogram was established based on a least absolute shrinkage and selection operator (LASSO)-derived logistic model. The discrimination and calibration ability of this nomogram was evaluated by Hosmer-Lemeshow test and calibration curves in the training and validation cohort. Results Of the 830 subjects with baseline zero score with the average follow-up period of 4.55±2.42 year in the study, these subjects were randomly placed into the training set or validation set at a ratio of 2.8:1. These study results showed in the 612 subjects with baseline zero score, 145 (23.69%) subjects developed CAC progression in the training cohort (N=612), while in the validation cohort (N=218), 51 (23.39%) subjects developed CAC progression. This LASSO-derived nomogram included the following 10 predictors: “sex”, age”, “hypertension”, “smoking habit”, “Gamma-Glutamyl Transferase (GGT)”, “C-reactive protein (CRP)”, “high-density lipoprotein cholesterol (HDL-C)”, “cholesterol”, “waist circumference”, and “follow-up period”. Compared with the FRS and ASCVD models, this LASSO-derived nomogram had higher diagnostic performance and lower Akaike information criterion (AIC) and Bayesian information criterion (BIC) value. The discriminative ability, as determined by the area under receiver operating characteristic curve was 0.780 (95% confidence interval: 0.731-0.829) in the training cohort and 0.836 (95% confidence interval: 0.761-0.911) in the validation cohort. Moreover, satisfactory calibration was confirmed by Hosmer-Lemeshow test with P values of 0.654 and 0.979 in the training cohort and validation cohort. Conclusions This validated nomogram provided a useful predictive value for subclinical coronary atherosclerosis in subjects with baseline zero score, and could provide clinicians and patients with the primary preventive strategies timely in individual-based preventive cardiology.